Computer aided instruction for three phase induction machine / Mohd Supian Selamat - Selamat, Mohd Supian (1999)
This project ilmiah present the Computer Aided Instruction (CAI) software developed using Visual Basic (VB) programming language. The software will assist the student in learning the three-phase induction machine. This software will guide the student on threephase induction machine lesson with the help of the simple notes in form of key point. The notes presented include examples, animated diagrams and pictures in order to make the learning more attractive and understandable. This software also contain quizzes, hence the student understanding coiild be tested at the end of the lesson. Last but not least this Project Ilmiah also elaborates the development and the implementation of the courseware for Computer Aided Instruction